Tingkat Keparahan Karies pada Siswa SDN Pandan di Desa Pandan, Kecamatan Pacet , Kabupaten Mojokerto - Sosiawan, Agung (FKG Unair, 2013)
Background: Based on the data of basic health research (RISKESDAS) in 2013, kids in elementary school (5-9 years old) suffers dental problem (28.9%) and kids in higher age (11-14 years old) also have dental problem (25.2%). DMF-T index in 12 years old kidsis 1.4. Pandan is one of the villages that located in Pacet, Mojokerto Residents, and until now the main health service (Puskesmas Pandan) does not have any specific data about their caries severity. Purpose: The aim of this study was to determine the caries severity in SDN Pandan students at Pandan, Pacet, Mojokerto. Method: This study was observational descriptive with cross sectional approach. The samples used were 110 students of 1st until 5th grade of SDN Pandan and taken by stratified proportional random sampling.Data were collected by conducting interviews, index PHP measurement by using disclosing agents, DMF-T and def-t measurement by intra-oral examination.Result: 92% children of SDN Pandan have higher level of caries severity than average (5.9). Conclusion:Caries severity in SDN Pandan students is affected by OH status, age, tooth formation, brushing tooth time, snack consistency, students knowledgement, parents’ education grade.